Pucking wild eaudiobook - Rath, Emily (Jacksonville Rays, 2023)
My name is Tess Owens, and my life is officially on fire. I never thought dancing at my best friend's wedding would be the match to light the flames. But with one lingering touch, one longing look . . . and one sneaky caterer holding a camera phone, my almost ex-husband is ready to torch my entire life. Unwilling to face the heat, I do what I do best: I run. Straight into the arms of Rachel and her team of NHL hockey players. One player stands apart from the rest. Jacksonville Rays star forward Ryan Langley is out with an injury. I get the surprise of my life when he shows up at my door, declaring himself my roommate. Now I have six weeks to launch a new business. Six weeks to fight for my freedom . . . all while fighting my growing attraction to this All-American sweetheart. Did I mention he's ten years younger than me? I want to believe him when he says age is just a number. I want to believe that our pasts don't define us forever. But first I have to stop running. With one innocent dance, Ryan Langley helped me start this fire. What if we're meant to fan these flames? What if, together, we're meant to burn? Contains mature themes.